Diagnostic Accuracy of Clinical Features, Laboratory Features, and Ultrasound Imaging Compared to Intraoperative Findings in Patients with Obstructive Jaundice - Yudith Meityana Hernandita; Tomy Lesmana; Alphania Rahniayu (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. Patients with obstructive jaundice have either benign or malignant underlying etiologies.2. Ultrasound imaging had the highest accuracy in diagnosing the etiology of obstructive jaundice among other examinations, such as clinical signs and laboratory tests. AbstractIntroduction: Jaundice due to biliary obstruction can be caused by a diverse group of diseases, including both benign and malignant etiologies. This study aimed to evaluate the accuracy of clinical features, laboratory features, and ultrasound imaging in diagnosing the etiology of obstructive jaundice with intraoperative findings as the gold standard.Methods: This was an observational cross-sectional analytic study conducted on 49 subjects by obtaining patients’ data from medical records in the Medical Record Center Dr. Soetomo General Academic Hospital, Surabaya. Collected data were statistically analyzed using a diagnostic test.Results: In this study, sensitivity (Sn), specificity (Sp), and accuracy of each feature in differentiating masses and stones as the etiology of obstructive jaundice were obtained. Progressive jaundice had Sn 88.2%, Sp 37%, and accuracy 56.8%. Complaints of fever had Sn 73.9%, Sp 90.9%, and accuracy 79.4%. Courvoisier’s law had Sn 61.5%, Sp 61.5%, and accuracy 61.5%. Serum CA 19-9 had Sn 75%, Sp 58.3%, and accuracy 67.9%. Ultrasound imaging had Sn 81.8%, Sp 100%, and accuracy 93.3%.Conclusion: Ultrasound imaging had the highest accuracy in diagnosing the etiology of obstructive jaundice, followed by complaints of fever, serum CA 19-9, Courvoisier’s law, and progressive jaundice, respectively.